Carbon emission strategies for container handling equipment using the activity-based method: A case study of Ambarlı container port in Turkiye. (March 2023) - Okşaş, Olgay
Abstract: One of the most important components of a port's sustainability is its environmental impact. Port operators are currently focusing on the sustainable development of ports to measure this environmental impact and determine the emissions inventory. To combat climate change globally, Turkiye envisages reduction of its greenhouse gas (GHG) emissions rate by 21% until 2030. In line with this target, container ports are also focusing on the sustainability of their environmental impact and determining their emissions inventory. This study aims to estimate the total carbon emissions produced by the container handling equipment (CHE) used in the container port operations and to plan the carbon emission reduction strategy as concerns the climate change adaptation policy. The Ambarlı container port, which handles approximately 30% of Turkiye's total container volume, has been chosen as the application area of this case study. Carbon emissions from CHE vehicles in the port were estimated using the activity-based method. The carbon emission value per TEU in 2021 is calculated as 0.011335 tCO2 e/TEU. Carbon emission reduction scenarios were created at two-year intervals until 2030. It has been determined that the dominant contribution to carbon emission in the container port is provided by terminal tractors that consume diesel fuel.